2022
DOI: 10.3389/fpsyg.2022.926779
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Style and Employees' Commitment to Service Quality: An Analysis of the Mediation Pathway via Knowledge Sharing

Abstract: Very little attention has been given to understanding the commitment to service quality and desirable outcomes in the hotel industry. This study investigates the impact of directive and participative leadership on the frontline commitment to service quality through the mediation of knowledge sharing. This will eventually help us to generate the employees' commitment to service quality (CSQ) desirable behavior. The survey was distributed to 37 hotels. A total of 235 frontline employees participated in the surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 113 publications
0
3
0
Order By: Relevance
“…Commitment and leadership style discussed by previous scholars indicated that leaders always positively influence employees' commitment (Pahi et al, 2009). Furthermore, these studies showed that leadership contributes to a healthy organisational environment, motivation, trust, and high morale, which is how staff members develop a sense of commitment to the organisation.…”
Section: Another Addsmentioning
confidence: 81%
“…Commitment and leadership style discussed by previous scholars indicated that leaders always positively influence employees' commitment (Pahi et al, 2009). Furthermore, these studies showed that leadership contributes to a healthy organisational environment, motivation, trust, and high morale, which is how staff members develop a sense of commitment to the organisation.…”
Section: Another Addsmentioning
confidence: 81%
“…They also found that female and male preference of leadership styles varies. Pahi et al, (2022) found different leadership styles would have different impact on staff commitment towards service quality.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Therefore, the organizations will have to ensure green practices as to lead the enterprises for green sustainable profitability (Bombiak & Marciniuk-Kluska 2018). Consequently, the green managers are supposed to train and develop green practices and green behaviors among the employees (Pahi et al, 2022). The HR need to improvise its working environment and performance styles.…”
Section: Introductionmentioning
confidence: 99%